Design and Development of Unit Cell and System for Vanadium Redox Flow Batteries (V-RFB) - M. R., Mohamed; S. M., Sharkh; H., Ahmad; M. N., Abu Seman; F. C., Walsh (Academic Journals, 2012)
Vanadium redox flow battery (V-RFB) has been attracted by many researches; some are under field testing and demonstration stage, but information on construction, experimental characterization, electrolyte preparation, overall systems under study, etc. are still limited. This paper focus on the technical issues faced and the lessons learnt during the development of unit cell and system for V-RFB. Firstly, brief description on problem identification, development and implementation in cell design and system for V-RFB are discussed. Secondly, preliminary experiment on 25 cm2 laboratory, unit cell V-RFB presents various difficulties such as its high tendency to fall under failure mode are presented. Finally, discussion on experimental result which shows significant improvement on V-RFB system efficiency up to 72% with reduction of contact resistance, recorded an average of 8.6 mΩ. In addition, the newly developed system provides a constructive base for future studies in temperature-controlled system and a divided, open-circuit potentiometric cell for half-cell redox analysis.